2023
DOI: 10.1108/jiabr-09-2022-0248
|View full text |Cite
|
Sign up to set email alerts
|

Government policy response to COVID-19 and bank performance: a comparison between Islamic and conventional banks

Abstract: Purpose This study aims to examine the joint impact of the COVID-19 pandemic and the government response on the performance of Islamic and conventional banks. Design/methodology/approach Data were collected from a sample of 94 conventional and 14 Islamic banks in Indonesia from March 2020 to September 2021. The system generalized methods of moments estimation is used to analyze the data. Findings This study finds robust results regarding the negative impact of the COVID-19 pandemic and the positive effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…This divergence in profitability dynamics during crises emphasizes the need for Islamic banks to adapt swiftly to evolving market conditions. In comparison to conventional banks, Islamic banks have poor performance (Yudaruddin, 2023b).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…This divergence in profitability dynamics during crises emphasizes the need for Islamic banks to adapt swiftly to evolving market conditions. In comparison to conventional banks, Islamic banks have poor performance (Yudaruddin, 2023b).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Moreover, prior research has also attempted to analyze the role of government responses, which has emerged as a critical factor in maintaining stability. Yudaruddin (2023) emphasized the pivotal role played by government actions in safeguarding both the conventional and Sharia-compliant banking sectors. This highlights the intricate connection between the financial industry and the broader sociopolitical context, underscoring how external factors significantly influence the performance of Islamic banks.…”
Section: The Impact Of Covid-19 On the Islamic Banking Industry In In...mentioning
confidence: 99%
“…Other research has identified that the financial sector is often affected by shocks that trigger global crises, such as the Asian financial crisis of 1997/1998 (Trinugroho et al ., 2014); the global financial crisis of 2007/2008 (Altunbas et al ., 2021); and the COVID-19 pandemic (Demir and Danisman, 2021; Maria et al ., 2022; Riadi et al ., 2022; Yudaruddin, 2023a, b). Prior to the Russian invasion of Ukraine, investors in the financial sector faced problems such as the COVID-19 pandemic, the impact of which was more profound than the global financial crisis (Riadi et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%